PENERAPAN STRATEGI PQ4R (PREVIEW, QUESTION, READ, REFLECT, RECITE, REVIEW ) TERHADAP HASIL BELAJAR KETRAMPILAN MEMBACA - PUTRASIWI, TYASAJI (Jurnal Pendidikan Khusus, 2017)
ABSTRACT Limitations in reading skills in children with hearing impairment caused by lack of vocabulary. This will hinder the process of capturing information. To solve the problem required innovation, one PQ4R strategy implementation. The purpose of this study to determine whether there is influence strategy implementation PQ4R the learning outcomes of reading skills of deaf students of class X Senior High School of Special Education Dharma Bhakti Patianrowo. The method used is quantitative research methods, the design of Pre-Experimental Design with the kind of One-group pretest-posttest design to compare the situation before and after beingtreated. The results showed that the value of Zh (2.20) and the Z table 5% (1.96), then to interpretation is Zh> Zt. So we can conclude that Ha accepted, meaning that there is the effect of applying PQ4R strategy on deaf children in class X in SMALB Dharma Bhakti Patianrowo.   Keywords: Implement strategies PQ4R, learning outcomes of   reading